2015
DOI: 10.3892/ol.2015.3991
|View full text |Cite
|
Sign up to set email alerts
|

Apelin-13 induces autophagy in hepatoma HepG2 cells through ERK1/2 signaling pathway-dependent upregulation of Beclin1

Abstract: Abstract. The aim of the present study was to investigate the effect of Apelin-13 on autophagy in hepatocellular carcinoma HepG2 cells and the underlying mechanism of the effect. The HepG2 cells were treated with Apelin-13 at a final concentration of 0.0001, 0.001, 0.01 and 0.1 µmol/l for 24 h. Cells were also treated with 10 µmol/l PD98059 for 24 h. The expression of the extracellular signal-regulated kinase (ERK)1/2, phosphorylated ERK1/2 (pERK1/2) and Beclin1 proteins were detected by western blot analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Studies have found that phosphorylation of Erk induces autophagy in human cervical cancer Hela cells (31) and liver cancer cells (22). We found that 40 nmol/l TPI could increase p-p38 MAPK and p-Erk expression after treatment for 24 h. Erk activation is closely related to autophagy induction (16,30,32).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Studies have found that phosphorylation of Erk induces autophagy in human cervical cancer Hela cells (31) and liver cancer cells (22). We found that 40 nmol/l TPI could increase p-p38 MAPK and p-Erk expression after treatment for 24 h. Erk activation is closely related to autophagy induction (16,30,32).…”
Section: Discussionmentioning
confidence: 84%
“…Autophagy is a conserved process aimed at maintaining cell homeostasis under normal and stress conditions (22). Above experiments showed that TPI induced MCF-7 cell apoptosis by Bax upregulation, as well as cleaved caspase-3 activation, which indicates that TPI induces cytotoxicity through the mitochondrial pathway.…”
Section: Tpi Likely Induces Autophagy Through Lc3b Protein Activationmentioning
confidence: 91%
“…In mammalian cells, BECN1 functions as part of a class III phosphatidylinositol 3-kinase, thus participating in the generation of phosphatidylinositol-3-phosphate, which is of critical significance in autophagy modulation [60]. Huang et al [61] recently demonstrated that the APLN (apelin) active peptide APLN13 induces autophagy in hepatoma HepG2 cells through a MAPK1/ERK2 signaling pathway-dependent upregulation of BECN1. Moreover, Shrivastava et al [62] reported that hepatitis C virus upregulates BECN1 for induction of autophagy and activates MTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…During stress conditions, the kinase mTOR is a critical regulator of autophagy induction. Phosphorylation of mTOR (p-mTOR expression) via ERK1/2 signaling regulates autophagic flux [7173]. Increasing evidence suggests that phosphorylation of ERK1/2 activates mTOR complexes by phosphorylation of mTOR [74].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that GMF interferes with the autophagy pathway by enhancing p-mTOR expression. In addition, expression of ERK1/2 modulates the mTOR expression via phosphorylation of mTOR [74,52,73]. …”
Section: Discussionmentioning
confidence: 99%